Intramolecular Path Determination of Active Electrons on Push‐Pull Oligocarbazole Dyes‐Sensitized Solar Cells - Trabelsi, Salma (ChemistryOpen, 2019)
Several push‐pull oligocarbazole dye‐sensitizers have been studied using theoretical methods in order to better understand the relationship between structural electronic or optical properties and intramolecular path of active electrons during the ionization and injection processes. DFT/TD‐DFT calculations were performed on a series of five dye sensitizers. They differ by the presence of electron donating group (EDG) by inductive effect (noted+I) or electron releasing group (ERG) by mesomeric effect (noted+M) or electron withdrawing group by inductive effect (noted‐I) on the pushed part of the dyes studied. Our work focused on the internal distribution of electrons in the different parts of dye that are the push/pull moieties and the π‐bridge. The study concerned the ground state, the electronic transition process and the excited state. In each situation, the fragment acting in the ionization or transition phenomena were identified. In the ground state, the electrons of the push part appear to be the least bound because they have the highest probabilities of ionization. In the excited state, the ionized atoms are essentially positioned in the pushing part and some neighboring atoms of the bridge. In the electronic transition, the active atoms are located in the π‐conjugated part but only on the side adjacent to the acceptor group. To arrive to this conclusion, we optimized the structures of the five dyes in their ground and excited states. We calculated the atomic charges, the wavelengths and intensities of electronic transitions in the visible domain, the reorganization energies as well as the oxidation potential. It appears that +M donor ligands improve the performance of a dye because the great distribution of atoms to be ionized in the push parts.